EKSPLORASI DAN KARAKTERISASI AZOTOBACTER INDIGENOUS UNTUK PENGEMBANGAN PUPUK HAYATI TANAMAN PADI GOGO LOKAL DI LAHAN MARJINAL - NURMAS, ANDI; -, NOFIANTI; RAHMAN, ABDUL; KHAERUNI, ANDI (Jurnal Agroteknos, 2014)
Azotobacter is bacterium that has the ability to fix nitrogen and produce hormone IAA, thus potentially acts as biofertilizer agent. There are differences in chemical, biological and other characters of Azotobacter strains. Some strains have higher ability to fix nitrogen than the others. Exploration and characterization are important to be done because the bacteria that provide nutrients and live free rhizosphere regions, possible have different abilities. In addition to N2 fixing, growth hormone production, phosphate dissolving, they are also tolerant to a certain temperature and pH. The purpose of the research was to obtain information and the latest data on indigenous Azotobacter that potential as a source of biofertilizer, and triggering factor for upland rice growth on marginal lands in Southeast Sulawesi. Exploration from several locations has selected 21 Azotobacter isolates. The test results indicated that the 21 Azotobacter isolates have the ability to produce IAA, dissolve phosphate and stable at pH 5.0-7.0. All 21 isolates tested had the ability to survive at 40oC, eight isolates i.e. LT2D1, LT2d2, LU2c, RG4c, MP1f, LT2d3, ML1j, and RR8awere able to survive at a temperature of 45o C, and LT2d1 isolate survived at temperatures 50oC. The results of the evaluation of the wet weight of upland rice seedlings selected 10 isolates that were: KU6e, MS3e, RG4c, RR8b1, LU2c, RB4b, MS3f, LU2c1, RJ5e, RR8b2 and evaluation of seedling dry weight selected 5 isolates that were: RB4b, LU2c, RJ5e, RR8b2, LT2d1. Keywords: exploration, characterization, indigenous Azotobacter, local upland rice